Dead money [videorecording (DVD)] - Wilcox, Josh; Hirsch, Emile, 1985-; Keith, David, 1954-; Culkin, Rory; Facinelli, Peter, 1973- (Samuel Goldwyn Films, 2024)
Professional poker player Andy and his girlfriend Chloe are involved in a crazy 24 hours after a home poker game is robbed. Andy finds up playing the largest poker game of his life as both of their lives are in danger.